Reconciling Surrogacy with Islamic Ethics: Maqāṣid al-Sharīʿa, Ijtihad, and Contemporary Legal Debates - Fadhilah, Nur; Musonnif, Ahmad; Alamsyah, Muhammad Nurravi (Sakina: Journal of Family Studies, 2025)
This study examines the diverse interpretations of Islamic jurisprudence on surrogacy, focusing on the contrasting approaches between Sunni and Shia scholars. While Sunni scholars predominantly prohibit surrogacy, citing concerns over lineage integrity, marital sanctity, and ethical risks, Shia jurisprudence, particularly in Iran, allows surrogacy under strict regulatory conditions. The study employs a qualitative legal methodology, incorporating Islamic legal texts, fatwas, national legislation, and comparative legal analysis to evaluate how different Islamic traditions approach surrogacy regulation. The findings reveal that Islamic legal thought on surrogacy remains deeply divided. Sunni-majority countries such as Saudi Arabia, Indonesia, and Pakistan uphold stringent bans on surrogacy, emphasizing the need to maintain clear parental lineage. Conversely, Iran’s legal framework permits surrogacy, integrating maqāṣid al-sharīʿa (higher objectives of Islamic law) to justify its permissibility under ethical guidelines. The study also explores bioethical concerns surrounding the commodification of childbirth and the exploitation of surrogate mothers, emphasizing the necessity of ethical oversight in surrogacy arrangements. The research underscores the importance of developing harmonized legal frameworks that balance Islamic ethical principles with contemporary reproductive needs. Greater interdisciplinary collaboration between Islamic scholars, legal practitioners, and medical experts is crucial for ensuring that surrogacy regulations in Muslim-majority countries are both ethically sound and legally coherent. Future studies should investigate cross-cultural experiences of Muslim couples engaging in surrogacy, regulatory best practices, and the impact of surrogacy laws on family dynamics in Islamic contexts.